2004
DOI: 10.1016/j.jacc.2003.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress echocardiography for noninvasive assessment and risk stratification of patients with rheumatic mitral stenosis

Abstract: In patients with MS, DSE is a safe and highly feasible stress test. A DSE-MG > or =18 mm Hg identifies a subgroup of high-risk patients in whom a more aggressive approach may be warranted; on the other hand, patients with a DSE-MG <18 mm Hg predicts an uneventful clinical course and may justify a more conservative strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 29 publications
5
49
0
6
Order By: Relevance
“…We found that; MVR showed the best correlation with NYHA functional class when compared to the anatomical determinants of MS severity and it is an independent predictor of NYHA class, this explain the major role of MVR in development of dyspnia, thus, MVR could be a complement to the other conventional methods used in assessment of MS. Our results are in agreement with Izgi, et al [10] and others [17][18][19][20].…”
Section: Discussionsupporting
confidence: 94%
“…We found that; MVR showed the best correlation with NYHA functional class when compared to the anatomical determinants of MS severity and it is an independent predictor of NYHA class, this explain the major role of MVR in development of dyspnia, thus, MVR could be a complement to the other conventional methods used in assessment of MS. Our results are in agreement with Izgi, et al [10] and others [17][18][19][20].…”
Section: Discussionsupporting
confidence: 94%
“…78 Studies using Doppler echocardiography have also demonstrated that mean and peak TMPG and PA systolic pressure significantly increase with exercise in patients with MS. 79 Dobutamine stress echocardiography has also been confirmed as an effective and safe modality for assessment of severity of RMS. 80 Reis et al found that a TMPG cut-off value of ≥ 18 mmHg during exercise is a predictor of future adverse clinical events in patients with RMS. 80 Because exercise is more physiologic, it is the recommended way of stress for evaluation of MS. ) who claim to be asymptomatic with daily activities would develop dyspnea during a stress test.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…80 Reis et al found that a TMPG cut-off value of ≥ 18 mmHg during exercise is a predictor of future adverse clinical events in patients with RMS. 80 Because exercise is more physiologic, it is the recommended way of stress for evaluation of MS. ) who claim to be asymptomatic with daily activities would develop dyspnea during a stress test. 81 Contrary to the previous guidelines, 82 current VHD guidelines do not include PA systolic pressure (peak exercise) as a criterion for diagnosis of severe MS.…”
Section: Stress Echocardiographymentioning
confidence: 99%
“…Reis et al [12] included 53 patients with moderate to severe MS and performed a DSE in all patients. After a mean follow-up of 60 months, 29 patients presented with cardiovascular complications.…”
Section: Exercise Echocardiography In Mitral Stenosismentioning
confidence: 99%